2x+6=93-9x

Simple and best practice solution for 2x+6=93-9x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+6=93-9x equation:


Simplifying
2x + 6 = 93 + -9x

Reorder the terms:
6 + 2x = 93 + -9x

Solving
6 + 2x = 93 + -9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9x' to each side of the equation.
6 + 2x + 9x = 93 + -9x + 9x

Combine like terms: 2x + 9x = 11x
6 + 11x = 93 + -9x + 9x

Combine like terms: -9x + 9x = 0
6 + 11x = 93 + 0
6 + 11x = 93

Add '-6' to each side of the equation.
6 + -6 + 11x = 93 + -6

Combine like terms: 6 + -6 = 0
0 + 11x = 93 + -6
11x = 93 + -6

Combine like terms: 93 + -6 = 87
11x = 87

Divide each side by '11'.
x = 7.909090909

Simplifying
x = 7.909090909

See similar equations:

| -69/7=w+1/7 | | t+7/9=13/9 | | k+2/5=39/35 | | 7t=14/5 | | 2/5b=-4/5 | | n/-7=-5 | | x/7=4/7 | | 4/9+w=55/63 | | d+2=16/9 | | 1+a=5/6 | | -19-4x=4x+17 | | w-2=8 | | n-9=-8 | | -1/2=k+1/2 | | n-7/10=-77/10 | | w+1/2=-3/10 | | t/-4=-1 | | -1/2k=-3/22 | | 13/5=k-2/5 | | 7=a+5 | | x-5/7=72/7 | | n/-3=6 | | 3/4+t=39/4 | | 4/9+w=-2/9 | | 2/3a=6 | | d+3/7=33/28 | | -62/7=a+1/7 | | 1+a=3/2 | | d+1=7/5 | | t-7=-19/3 | | n/-2=7 | | b-10=-19/2 |

Equations solver categories